Tapeséré Akorang Mabbasa Ogi - Teguh Arafah (Al-Fanar: Jurnal Ilmu Al-Qur’an dan Tafsir, 2018)
Many indigenous Muslims compose a book of interpretation with different types of languages ​​and methods used. Then came the mention of "native" interpretation, which is a term used to refer to the interpret. literature that arose/ appear from the creation of the Muslim of Archipelago, both the original and the descendants. For example Tarjumân Mustafîd by 'Abd Rauf Singkel using Malay Language, Al-Ibrîs li Ma'rifat at-Tafsîr Al-Qur’an al-'Azîz karya KH Bishri Musthafâ using Javanese Language, Tahrîf Qulûb al-Mu'minîn fî Tafsîr Sentences Sûrat Yâsîn creation of Ahmad Sanusi ibn 'Abd Rahim. In this article, attempt to reveal one of the literary interpretation of the archipelago from Tana Bugis AGH. Abd Muin Yusuf with his creation TapeséréAkorang Mabbasa Ogi with the Indonesian Council of Ulama (MUI) of South Sulawesi. This book is called the book of Tapesere Akorang Mabbasa Ogi. Its Naming as a practical consideration to facilitate the reader to know and remember the book for the society of Bugis easily achieve the purpose of Al-Qur’an, both in the activities of religion and daily life.The Book of Tafsere Akorang mabbasa Ogi when viewed in term of its presentation belongs to the category of Tahlili Interpretation, but in the description does not use such a performance with interpretations using this method. By analyzing different aspects in detail, especially the linguistic aspect. It is intended to facilitate the reader Interpretation not to be preoccupied with his analyzes.